PERFORMANCE ANALYSIS OF CLUSTERING MODELS BASED ON MACHINE LEARNING IN STUNTING DATA MAPPING - Handayani, Masitah; Sibuea, Mustika Fitri Larasati (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Stunting is one of the nutritional problems that the world pays the most attention to and a major nutritional problem in Indonesia. Stunting is a problem in toddler growth which is characterized by a toddler's height that is too short compared to toddlers of his age. In the research location, namely Asahan Regency, the mapping of areas prone to increased stunting rates has not been carried out optimally. The process of exploring the stunting data warehouse is useful for adding information that can assist the government in making policies. Therefore, the aim of this research is to map stunting-prone areas in Asahan district based on the number of stunting cases in Asahan district using the machine learning-based K-Means clustering model. Based on previous research reviews, the k-means clustering method used has not used the normalization process. In addition, distance measurement only uses Euclidean Distance. Meanwhile, in this research, clustering performance analysis was carried out using a more in-depth process, namely by applying data normalization at the beginning, using the elbow method to determine the best number of clusters (K), measuring distance using Euclidean Distance, Manhattan Distance and Minkowski Distance to obtain comparison results. better clusters. The analysis results show that the best number of clusters is cluster 2 which shows the mapping results into 2 groups with a DBI of 0.51290 and a silhouette_score of 0.71432. Keywords: stunting; k-means clustering; machine learning Abstrak: Stunting menjadi salah satu permasalahan gizi yang paling diperhatikan dunia dan permasalahan gizi yang utama di Indonesia. Stunting merupakan masalah pada pertumbuhan balita yang ditandai dengan tinggi badan balita yang terlalu pendek dibanding balita seusianya. Pada lokasi penelitian yaitu Kabupaten Asahan, pemetaan daerah rawan peningkatan angka stunting belum dilakukan dengan optimal. Proses eksplorasi gudang data stunting ini berguna untuk menambah informasi yang dapat membantu pemerintah dalam mengambil kebijakan. Maka dari itu, tujuan dari penelitian ini adalah pemetaan daerah rawan stunting di kabupaten Asahan berdasarkan jumlah kasus stunting di Kabupaten Asahan menggunakan model clustering metode K-Means berbasis machine learning. Berdasarkan tinjauan penelitian terdahulu, metode k-means clustering yang digunakan belum menggunakan proses normalisasi. Selain itu, pengukuran jarak hanya menggunakan Euclidean Distance. Sedangkan dalam penelitian ini, analisis kinerja clustering yang dilakukan dengan proses yang lebih mendalam yaitu dengan penerapan normalisasi data di awal, penggunaan elbow method untuk penentuan jumlah cluster (K) terbaik, pengukuran jarak dengan Euclidean Distance, Manhattan Distance dan Minkowski Distance untuk mendapatkan hasil perbandingan cluster yang lebih baik. Hasil analisis menunjukkan bahwa jumlah cluster terbaik yaitu  cluster 2 yang menunjukkan hasil pemetaan menjadi 2 kelompok dengan DBI 0.51290 dan silhouette_score sebesar 0.71432. Kata kunci: stunting; k-means clustering; machine learning